Perspectivas em derivadas de ordem superior de funções quaterniônicas - RIBEIRO, Marcelo Oliveira (2019)
The dissertation consists essentially of the study of quaternions, aiming to generalize the results of Classical Complex Analysis, as well as to base theoretical bases for future applications to Mathematics and Physics. For this, we show the structure of the quaternions and their properties, we define the main quaternionic functions, we present relations of the type Cauchy-Riemann, we show quaternionic derivatives for a class of functions, we determine results with respect to the derivation of superior order and we show the generalization of the Cauchy integral formula.